Evaluation of the Physicochemical Characteristics of Honey Produced by Honey Bees (Apis mellifera) in Waghimra Zone - Ebrahim, Yesuf (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Honey is a natural sweet substance produced by bees from plant nectar or secretions. This study focused on assessing the physicochemical properties of honey from the Waghimra Administrative zone in Ethiopia's Amhara region, and examining how different agro-ecological zones (lowland, midland, and highland) and sampling sources (beekeepers, SDARC apiary site, and local honey traders) influence honey quality. A total of 27 honey samples were collected across these agro-ecological areas. Physicochemical characteristics were analyzed following international standards, including the European Union Directive 2001/110/EC and guidelines from the Ethiopian Standards Agency (2011). The findings showed that the average moisture content, pH, ash content, HMF (hydroxymethylfurfural), free acidity, electrical conductivity, total solids, reducing sugars, and apparent sucrose levels were 17.16%, 3.56, 0.1g/100g, 1.99mg/kg, 24.17meq/kg, 0.25mS/cm, 82.84%, 66.68g/100g, and 4.29g/100g, respectively. All these values were within the acceptable ranges set by the Quality and Standards Authority of Ethiopia, Codex Alimentarius, and European Union standards, confirming the honey's high quality.